(3HfGJ GdCacGQ aj eYGfi GdGNHGQs - (3eMeO Hf Ydj Hf CMeO Hf Ydj Hf NeGQhjg Hf Whdhf GdOeTbqj GdUGdMj GdMfaj, TeS GdOjf , J (B953 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi LRjd aVdg GdGced hGdUdGI hGdSdGe agPG JYdjb SeJg HfGJ GdGacGQ ai eYGfi GdGNHGQ s
(3BNQgG (B:s
(3acJHJ dg gPg GdGQHYjf GdWHjI edNUI hbO cfJ cJHJ ai gPG GdeYfi eDdajf CMOgeG eSfO hGdGNQ eaUd s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B291s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI eJhSWI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs